THE EFFECT OF INVESTMENT AND INFRASTRUCTURE ON ECONOMIC INEQUALITY IN THE REGENCIES/MUNICIPALITY OF BALI PROVINCE BALI - Hilda Nurhidayati; Ni Luh Karmini (Adisam Publisher, 2026)
Economic inequality in Bali Province remains concentrated in the southern region due to the dominance of the tourism sector. This quantitative study analyzes the effects of Domestic Investment (PMDN), Foreign Direct Investment (PMA), road infrastructure, access to improved drinking water, and digital infrastructure on economic inequality (Gini Ratio) across the nine regencies/municipality of Bali during the 2017–2025 period. The analysis employs panel data regression using the selected Random Effect Model (REM) with robust standard errors clustered at the regency/municipality level. The estimation results indicate that, simultaneously, all variables have a significant effect on economic inequality (Wald chi2 = 46.15; Prob > chi2 = 0.0000). However, partially, only digital infrastructure is found to have a negative and statistically significant effect (one-tailed p = 0.001), confirming its role as the only consistent and robust economic equalizer. Domestic Investment (PMDN) and road infrastructure exhibit positive coefficient directions consistent with the initial hypotheses but are not statistically significant at the 5 percent significance level after correcting the standard errors. Meanwhile, Foreign Direct Investment (PMA) and access to improved drinking water have no significant effect, with coefficient directions opposite to the hypotheses, reflecting the weak linkage of enclave-type foreign investment in the tourism sector as well as the achievement of relatively equal service coverage (ceiling effect) for drinking water across all regencies/municipality in Bali. These findings support the relevance of the Cumulative Causation Theory (Myrdal) and the Endogenous Growth Theory (Romer), while also emphasizing the importance of correcting standard errors in panel data with a limited number of clusters. The policy implications highlight the need to accelerate digital infrastructure development in lagging regions as the highest priority for achieving more equitable economic development in Bali Province.